2010
DOI: 10.1007/s10126-010-9329-4
|View full text |Cite
|
Sign up to set email alerts
|

A Reverse Genetics System for the Great Lakes Strain of Viral Hemorrhagic Septicemia Virus: the NV Gene is Required for Pathogenicity

Abstract: Viral hemorrhagic septicemia virus (VHSV), belonging to the genus Novirhabdovirus in the family of Rhabdoviridae, causes a highly contagious disease of fresh and saltwater fish worldwide. Recently, a novel genotype of VHSV, designated IVb, has invaded the Great Lakes in North America, causing large-scale epidemics in wild fish. An efficient reverse genetics system was developed to generate a recombinant VHSV of genotype IVb from cloned cDNA. The recombinant VHSV (rVHSV) was comparable to the parental wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 32 publications
3
72
0
1
Order By: Relevance
“…Recombinant VHSVs harboring the D62A and D62A E181A mutations were generated using a reverse-genetics system (53). Recombinant viruses containing the mutant M genes were viable and were compared to recombinant WT (rWT) VHSV in a series of cell-based studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant VHSVs harboring the D62A and D62A E181A mutations were generated using a reverse-genetics system (53). Recombinant viruses containing the mutant M genes were viable and were compared to recombinant WT (rWT) VHSV in a series of cell-based studies.…”
Section: Resultsmentioning
confidence: 99%
“…Expression vectors for EPC MAVS and EPC IFN were obtained from Michel Brémont (French National Institute for Agricultural Research, Jouy-en-Josas, France), the VHSV L expression plasmid was reported previously (53), the Tet-mSEAP construct was obtained from Fan Dong (University of Toledo, Toledo, OH, USA), and the IFN-luciferase reporter was obtained from John Hiscott (Istituto PasteurFondazione Cenci Bolognetti, Rome, Italy). Other plasmids used included the IFN-induced transmembrane 1 (IFITM1)/luc plasmid (derived from pDW9-27CD2), SV40/␤-galactosidase (␤-Gal) (Promega), and SV40/luc (modified from SV40/␤-Gal).…”
Section: Methodsmentioning
confidence: 99%
“…This method involves the expression of a full-length positive-strand (antigenomic) RNA of the virus genome by vaccinia-driven T7 RNA polymerase (Fuerst et al, 1994;Schnell et al, 1986). After this recovery, many negative-strand RNA viruses have been recovered using similar technique, including human respiratory syncytial virus (Collins et al, 1995), vesicular stomatitis virus (Lawson et al, 1995) and three fish rhabdoviruses: snakehead rhabdovirus (Johnson et al, 2000), infectious hematopoietic necrosis virus (IHNV) (Biacchesi et al, 2000) and viral hemorrhagic septicemia virus (VHSV) (Ammayappan et al, 2011). However, no efforts have been continued for the development of reverse genetics system for SVCV.…”
Section: Genetic Diversity Amongst Svcv Strainsmentioning
confidence: 99%
“…아울러 바이러스 의 유전자들이 바이러스 복제 과정에 필수적이기 때문에 특정 바이러스 유전자들의 결핍은 세포 수준에서가 아니라 어류 개체에서의 바이러스 유전자들의 기능을 연구하는데 활용되 고 있다 [2,17]. 또한 rVHSV 결실 실험을 이용하여 NV 유전자 가 중요한 병원성 기능을 가지고 있음이 확인되었다 [8].…”
Section: 서 론unclassified